Evaluation of hypothalamus‐pituitary‐thyroid axis function by chronic perchlorate exposure in male rats. Issue 2 (15th November 2017) - Serrano‐Nascimento, Caroline; Calil‐Silveira, Jamile; Dalbosco, Rafael; Zorn, Telma Tenorio; Nunes, Maria Tereza
Abstract: Perchlorate is a widespread endocrine disruptor that was previously correlated with increased serum TSH levels and decreased thyroid hormones production both in animals and humans. Even so, the regulation of gene/protein expression in the hypothalamus, pituitary and thyroid by chronic perchlorate exposure was not completely elucidated. Therefore, this study aimed to investigate the underlying mechanisms involved in the disruption of hypothalamus‐pituitary‐thyroid axis by chronic perchlorate exposure. Male Wistar rats were treated or not with NaClO4 in the drinking water (35 mg/Kg/day) for 60 days. Thereafter, hormone/cytokines serum levels were measured through multiplex assays; genes/proteins expression were investigated by qPCR/Western Blotting and thyroid morphology was evaluated through histological analysis. Serum TSH levels were increased and serum T4 /T3 levels were decreased in perchlorate‐treated animals. This treatment also altered the thyrotropin‐releasing hormone mRNA/protein content in the hypothalamus. Additionally, the expression of both subunits of TSH were increased in the pituitary of perchlorate‐treated rats, which also presented significant alterations in the thyroid morphology/gene expression. Furthermore, perchlorate exposure reduced liver Dio1 mRNA expression and increased the content of pro‐inflammatory cytokines in the thyroid and the serum. In conclusion, our study adds novel findings about the perchlorate‐induced disruption of the hypothalamus‐pituitary‐thyroid axis gene/protein expression in male rats. The data presented herein also suggest that perchlorate induces thyroid and systemic inflammation through the increased production of cytokines. Taken together, our results suggest that perchlorate contamination should be monitored, especially in the individuals most susceptible to the deleterious effects of reduced levels of thyroid hormones.